Accuracy analysis of different surface reconstruction modelling methods for heritage objects digitized considering photogrammetric Data - Sužiedelytė-Visockienė, Jūratė; Kumetaitienė, Aušra; Bagdžiūnaitė, Renata (Geodesy and Cartography, 2011)
The article explains the possibilities of reconstructing heritage objects. Measurements were made using photogrammetric data received from digital images taken by the Canon EOS 1D Mark III digital camera calibrated in the Institute of Photogrammetry at the University of Bonn (Germany). The images were received applying the PhotoMod photogrammetric software produced in Russia. TIN (Triangulated Irregular Network) and an orthophoto map were made in the investigated objects. The modelling analysis of TIN data was made using ArcGIS software. The purpose of the article is to reconstruct the surface of heritage objects referring to photogrammetric data, to investigate accuracy dependence of heritage object reflection on the methods of preparing the initial data and to evaluate the influence of modelling methods on to the accuracy of reconstructing heritage objects when modelling photogrammetric data and selecting the most appropriate method of modelling parameters to restore the most accurate surface of the heritage object. Skirtingų reljefo modeliavimo metodų, sudarytų pagal paveldo objekto fotogrametrinius duomenis, tikslumo analizė Santrauka. Straipsnyje aprašomos paveldo – architektūrinio objekto paviršiaus modeliavimo galimybės. Modeliavimas atliktas pagal fotogrametrinius objekto duomenis–skaitmenines nuotraukas, darytas kalibruota fotokamera Canon EOS 1D Mark III. Kamera kalibruota Bonos universiteto Fotogrametrijos institute (Vokietija). Objekto nuotraukos apdorotos fotogrametrine kompiuterine programa PhotoMod (Rusija). Sudaryta objekto ortofotografinė nuotrauka ir, parenkant skirtingus duomenų šaltinius, paviršiaus TIN (triangulated irregular network). Skirtingais metodais, naudojantis ArcGIS programa, atliktas fotogrametrinių TIN duomenų modeliavimas ir gauti objekto paviršiaus vaizdai. Įvertintas rezultatų tikslumas ir kokybė. Reikšminiai žodžiai: paveldo objektas, skaitmeninė kamera, foto vaizdai, trianguliacija, ortofotorgafinės nuotraukos žemėlapis, TIN, paviržiaus modelis. Анализ точности разных методов моделирования поверхности, составленных в соответствии с фотограмметрическими данными объекта архитектурного наследия Резюме. Описываются возможности моделирования поверхности объекта архитектурного наследия. Моделирование осуществляется с использованием фотограмметрических данных объекта – цифровых снимков, снятых калибрированной цифровой камерой Canon EOS 1D Mark III. Камера калибрирована в Институте фотограмметрии Боннского университета (Германия). Снимки объекта обработаны по фотограмметрической компьютерной программе PhotoMod (Россия). Cделан ортофотографический снимок объекта и с помощью разных источников данных TIN (Triangulated Irregular Network) поверхности. Используя программу ArcGIS, разными методами проведено моделирование фотограмметрических TIN данных и получены изображения поверхности объекта. Осуществлена оценка точности и качества результатов. Ключевые слова: объект архитектурного наследия, цифровая камера, триангуляция, ортофотографический снимок объекта, TIN , модель поверхности. First published online: 07 Jul 2011